Pendidikan Kristen Sebagai Fondasi Etis teologis dan Moral Pada Generasi Alpha Dalam Menghadapi Realitas Zaman - Reni Triposa; Ruhut Parningotan Tambunan (Sekolah Tinggi Teologi Kanaan Nusantara, 2026)
The development of digital technology significantly shapes the living environment of Generation Alpha from an early age. Unlimited access to information poses moral, character, and spiritual challenges for the contemporary Generation Alpha. Christian education is necessary to build integrity, responsibility, ethical discernment, and sustainable Christian character. The phenomenon of digital culture reinforces moral relativism, the pursuit of social validation, consumerism, and a weakening of spiritual discipline. This study aims to analyze Christian education as the moral foundation for Generation Alpha in facing the realities of the times. The study employs a qualitative phenomenological approach using thematic analysis, phenomenological interpretation, and reflective theological synthesis. The results show that Christian education strengthens Generation Alpha’s faith identity, character, and ethical responsibility. Digital literacy, spirituality, and the exemplary conduct of educators bolster moral resilience in the face of contemporary cultural changes. This study proposes the Christian Transformative Moral Formation Model for the moral formation of Generation Alpha in a digital context. The model integrates Biblical Formation, Christlike Character, Digital Ethical Discernment, and Transformative Christian Living. Christian education contributes to building sustainable moral steadfastness, spirituality, and digital literacy among Generation Alpha. Further research is recommended to test the model’s effectiveness through field studies and ongoing empirical approaches.AbstrakPerkembangan teknologi digital membentuk lingkungan hidup generasi alpha sejak usia dini secara signifikan. Akses informasi tanpa batas meningkatkan tantangan moral, karakter, dan spiritualitas generasi alpha kontemporer. Pendidikan Kristen diperlukan membangun integritas, tanggung jawab, discernment etis, dan karakter Kristiani berkelanjutan. Fenomena budaya digital memperkuat relativisme moral, validasi sosial, konsumerisme, dan melemahnya disiplin spiritual. Penelitian bertujuan menganalisis pendidikan Kristen sebagai landasan moral generasi alpha menghadapi realitas zaman. Penelitian menggunakan pendekatan fenomenologi kualitatif dengan analisis tematik, interpretasi fenomenologis, dan sintesis teologis reflektif. Hasil penelitian menunjukkan pendidikan Kristen memperkuat identitas iman, karakter, dan tanggung jawab etis generasi alpha. Literasi digital, spiritualitas, dan keteladanan pendidik memperkuat ketahanan moral menghadapi perubahan budaya kontemporer. Penelitian menawarkan Christian Transformative Moral Formation Model bagi pembentukan moral generasi alpha kontekstual digital. Model mengintegrasikan Biblical Formation, Christlike Character, Digital Ethical Discernment, dan Transformative Christian Living. Pendidikan Kristen berkontribusi membangun keteguhan moral, spiritualitas, dan literasi digital Generasi alpha berkelanjutan. Penelitian selanjutnya disarankan menguji efektivitas model melalui kajian lapangan dan pendekatan empiris berkelanjutan.